Analysis of Character Design in Gacha Games through Manga Matrix Theory - Dean Mervyn; Eryc Eryc (Universitas Internasional Batam, 2024)
Character design is the most important asset in Gacha Games because we can display complex implied messages in a fictional character in a visual form that is easier to understand. This research aims to determine what makes players want to get this character and whether character design can influence the interest value in a gacha game. This research was carried out using a comparative qualitative method by analyzing the characters through Mounsey's holistic character designs, which were visually deepened by dissecting the characters using three stages of the manga matrix: the Form Matrix, Costume Matrix, and Personality Matrix. The authors will select the character samples taken from different gacha games. The selection of character samples from different gacha games allows research conducted by researchers to reveal comparisons of variations in character designs from different games. Based on the results of the analysis above, it can be concluded that the abilities, design, or background of a character are factors that make players want to get that character. Apart from that, the attributes possessed by a character influence interest in a game. The third thing can influence whether a game is good or bad and attract the attention of players to play the gacha game.